Description of Hospitalizations due to the Severe Acute Respiratory Syndrome Coronavirus 2 Omicron Variant Based on Vaccination Status. (25th August 2022) - Moffa, Matthew A; Shively, Nathan R; Carr, Dustin R; Bremmer, Derek N; Buchanan, Carley; Trienski, Tamara L; Jacobs, Max W; Saini, Vikram; Walsh, Thomas L
Abstract: Background: Limited descriptive data exist regarding the clinical characteristics of hospitalizations due to the severe acute respiratory syndrome coronavirus 2 Omicron variant based on vaccination status. Methods: This was a retrospective cohort study of all patients hospitalized with a diagnosis of coronavirus disease 2019 (COVID-19) between 15 January 2022 and 15 February 2022 across 9 hospitals in a large health network. Data were extracted by manual records review. Results: A total of 351 of 452 (77.7%) unvaccinated, 209 of 331 (63.1%) fully vaccinated, and 107 of 163 (65.6%) boosted patients hospitalized with a COVID-19 diagnosis were determined to be admitted specifically due to COVID-19 ( P < .001). Most (85%) boosted patients admitted due to COVID-19 were at least 65 years old and/or had severe immunosuppression, compared to 72.2% of fully vaccinated and 60.7% of unvaccinated patients ( P < .001). Significantly more unvaccinated patients (34.2%) required >6 L/minute of supplemental oxygen compared to fully vaccinated (24.4%) and boosted (25.2%) patients ( P = .027). The age-adjusted vaccine effectiveness (VE) against hospitalization due to COVID-19 was estimated to be 81.1% and 94.1% for full vaccination and boosted status, respectively, whereas VE against mortality related to COVID-19 was estimated to be 84.7% and 94.8%, respectively. Conclusions: During the Omicron BA.1 sublineage wave, unvaccinated patients hospitalized with a COVID-19 diagnosis were more likely than vaccinated patients to be admitted specifically due to COVID-19. Despite being younger with fewer comorbidities, unvaccinated patients required higher levels of care. Vaccination with a booster provides the greatest protection against hospitalization and death from COVID-19. Abstract : During the Omicron BA.1 sublineage wave, unvaccinated patients hospitalized with a COVID-19 diagnosis were more likely than vaccinated patients to be admitted specifically due to COVID-19. Despite being younger with fewer comorbidities, unvaccinated patients required higher levels of care.